O pewnym modelu stochastycznym procesu filtrowania płynów - BOROWIK, Stanisław; REDMER, Brunon (Engineering Transactions, 1970)
On a certain stochastic model of the filtrating process of fluidsIn the paper a theory of stochastic model of the fluid filtering process by means of a parous barrier is presented. Basic relations expressing the quantity and probability distribution of the particle dimensions in the fluid after the filtering and change of filtering properties of the porous barrier were derived. In spite of the fact that the assumed model is a simplification of the real process, the obtained results were confirmed by experiment.